Templates of Lymph Node Dissection for Renal Cell Carcinoma: A Systematic Review of the Literature - Campi, Riccardo; Sessa, Francesco; Di Maida, Fabrizio; Greco, Isabella; Mari, Andrea; Takáčová, Tána; Cocci, Andrea; Fantechi, Riccardo; Lapini, Alberto; Serni, Sergio; Carini, Marco; Minervini, Andrea (Frontiers in Surgery, 2018)
Background: The role of lymph node dissection (LND) for renal cell carcinoma (RCC) is controversial. Notably, the conflicting evidence on the benefits and harms of LND is inherently linked to the lack of consensus on both anatomic templates and extent of lymphadenectomy. Herein, we provide a detailed overview of the most commonly dissected templates of LND for RCC, focusing on key anatomic landmarks and patterns of lymphatic drainage. Methods: A systematic review of the English-language literature was performed without time filters in July 2018 in accordance to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement recommendations. The primary endpoint was to summarize the most commonly dissected templates of LND according to the side of RCC. Results: Overall, 25 studies were selected for qualitative analysis. Of these, most were retrospective. The LND template was heterogeneous across studies. Indications and extent of LND were either not reported or not standardized in most series. The most commonly dissected template for right-sided tumors included hilar, paracaval, and precaval nodes, with few authors extending the dissection to the inter-aortocaval, retrocaval, common iliac or pre/paraaortic nodes. Similarly, the most commonly dissected template for left-sided tumors encompassed the renal hilar, preaortic and paraaortic nodes, with few authors reporting a systematic dissection of inter-aortocaval, retro-aortic, common iliac, or para-caval nodes. Conclusions: In light of the unpredictable renal lymphatic anatomy and the evidence from available prospective mapping studies, the extent of the most commonly dissected templates might be insufficient to catch the overall anatomic pattern of lymphatic drainage from RCC.